Reusing railway infraestructures in the spirit of circular construction. A contribution to an operational concept - Ana Cardoso de Matos; Fernanda de Lima Lourencetti (Vitruvio: International Journal of Architectural Technology and Sustainability)
This paper aims to be a contribution to establish a position to the reuse of obsolete railway buildings in the field of circular construction. Recent discussions argue that considering that the circular economy is only related to the use of materials or waste is a misconception. The reuse of buildings is also an issue circular architecture. The European Union itself, since 2002, supports the Programme ESPON - European Territorial Cooperation Programme, which incisively inserts obsolete buildings in the "spirit of the circular economy", giving greater attention to industrial areas undergoing change and deindustrialisation. Considering that the concepts of circular construction and circular architecture originated in the circular economy, which emerged as a way to promote and ensure urban sustainability, this article addresses in a first moment the concept of circular construction from the first documents developed in the context of sustainable development to the latest policies proposed by ESPON. It also analyses the reuse of obsolete railway spaces based on the analysis of some emblematic examples of reuse, namely the Musée d'Orsay and the Promenade Plantée in Paris. These two examples represent different types of railway infrastructure and their fate will frame the reuse of railway buildings within the concept of circular construction.